Evaluasi Sistem Manajemen Pendidikan Dalam Meningkatkan Efektivitas Pembelajaran Di Ponpes Tahfiz Haji Nur Abdullah Yayasan Ibnu Abdul Aziz - Hidayati, Rahmi; Efnaliza, Efnaliza; Yuliani, Tri (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to evaluate the education management system in improving the effectiveness of learning at the Tahfiz Haji Nur Abdullah Islamic Boarding School, Ibnu Abdul Aziz Foundation. The background to this research stems from the importance of good management in creating an effective learning process, especially in the context of tahfiz education which requires special attention in time management, teaching methods and supporting facilities. The aim of this research is to identify the strengths and weaknesses in the educational management system implemented, as well as finding solutions to improve the quality of learning. The method used is a qualitative approach with data collection techniques through in-depth interviews, direct observation and documentation analysis. Respondents in this research involved Islamic boarding school managers, teachers and students. The research results show that although the management system implemented is quite effective, there are several obstacles, such as limited facilities, low quality of teacher training, and lack of regular evaluation of the learning process. In conclusion, to increase the effectiveness of learning at the Tahfiz Haji Nur Abdullah Islamic Boarding School, improvements are needed in terms of human resource management, curriculum development, and the provision of more adequate facilities.